2021
DOI: 10.7554/elife.64302
|View full text |Cite
|
Sign up to set email alerts
|

Residue-by-residue analysis of cotranslational membrane protein integration in vivo

Abstract: We follow the cotranslational biosynthesis of three multi-spanning E. coli inner membrane proteins in vivo using high-resolution Force Profile Analysis. The force profiles show that the nascent chain is subjected to rapidly varying pulling forces during translation, and reveal unexpected complexities in the membrane integration process. We find that an N-terminal cytoplasmic domain can fold in the ribosome exit tunnel before membrane integration starts, that charged residues and membrane-interacting segments s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(74 citation statements)
references
References 51 publications
(44 reference statements)
3
70
0
1
Order By: Relevance
“…To understand how the biochemistry of cotranslational protein translocation quantitatively impacts the force exerted on the nascent substrate, Hessa and colleagues have recently measured the protein translocation force in mammalian Sec61 translocon. [49] Their approach takes advantage of the ribosome arrest peptide (RAP) [50][51][52] of X-box binding protein 1 (Xbp1).…”
Section: Measuring Translocational Force With a Ribosome Arrest Peptidementioning
confidence: 99%
“…To understand how the biochemistry of cotranslational protein translocation quantitatively impacts the force exerted on the nascent substrate, Hessa and colleagues have recently measured the protein translocation force in mammalian Sec61 translocon. [49] Their approach takes advantage of the ribosome arrest peptide (RAP) [50][51][52] of X-box binding protein 1 (Xbp1).…”
Section: Measuring Translocational Force With a Ribosome Arrest Peptidementioning
confidence: 99%
“…Recent evidence has implicated the EMC in helping to establish the topology of the first TM of many GPCRs and likely other proteins [ 12 , 72 ]. The translocon’s lateral gate allows direct sampling of the membrane environment by the TM [ 73 ], possibly from the moment of its encounter with the translocon [ 39 , 74 ]. The code for insertion, i.e., what sequences partition to the membrane vs. remain in the channel, has been determined in exquisite detail with extensive, elegant experiments from von Heijne, White, and colleagues in the mid-2000s [ 31 , 32 ].…”
Section: Route Into Through and Out Of The Transloconmentioning
confidence: 99%
“…While the energetics of membrane insertion of transmembrane helices (TMHs) has been extensively studied both in vitro and in vivo [36], it is only recently that methodologies have been developed that make it possible to follow step-by-step the membrane insertion of individual TMHs as they come out of the ribosome exit tunnel. Two methods in particular can provide this kind of information: in vitro real-time FRET analysis of cotranslational membrane insertion [7] and in vivo Force Profile Analysis (FPA) where a translational arrest peptide (AP) engineered into the polypeptide chain is used to detect the force generated on the nascent chain during membrane insertion [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we applied FPA to three E. coli inner membrane proteins: EmrE, GlpG, and BtuC [9]. For all three proteins (a total of 20 TMHs), we found that, on average, a TMH starts to generate force on the nascent chain when its N-terminal end is ~45 residues away from the polypeptide transferase center (PTC) in the large ribosome subunit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation